Perbedaan Posisi Bibir Setelah Perawatan Ortodonti Dengan Ekstraksi Premolar Pertama Menggunakan Analisis Ricketts : Kajian pada Sefalogram Lateral di Klinik Ortodontis Bandung (Laporan Penelitian) - Diandra Christina; Yuniar Zen (Fakultas Kedokteran Gigi Universitas Trisakti, 2021)
Background: The difference in facial profile after orthodontic treatment is important in orthodontic treatment as one of the goals of orthodontic treatment is to improve facial esthetic. Convex facial profiles that require first premolar extraction are the most common complaints of orthodontic patients in Asia. This profile is characterized by an increased lip profile procumbency. Therefore, any difference in the position of the lips from before and after orthodontic treatment is needed to be evaluated. Some studies proved that there was a significant difference in lip position after orthodontic treatment with the extraction of the first premolar teeth. Ricketts analysis is widely used to determine clinical differences in lip position. Objective: To determine the difference in lip position after orthodontic treatment with extraction of the first premolar using Ricketts analysis. Methods: This study was observational analytic with a cross-sectional study design. The study was conducted on 30 samples of lateral cephalogram radiographs before and after treatment at Orthodontist Clinic Bandung. The difference in lip position after orthodontic treatment and extraction of the first premolar teeth was determined using the Ricketts analysis. The measurement results were statistically analyzed with paired T-tests. Result: There was a difference in the position of the upper and lower lips after orthodontic treatment with first premolar extraction with p <0.001. The distance of the upper and lower lips to the E-line after orthodontic treatment with first premolar extraction was different than before treatment. Conclusion: There is a significant difference of upper and lower lip position before and after orthodontic treatment with first premolar extraction.